Educational Challenges of Migrants’ Children at Home and School: Teachers, Learners and Caregivers’ Perspectives - Winniefridah Matsa (Springer, Cham, 2023)
Migrant children face formidable challenges at home and school as a result of absence of parents due to labour migration. The challenges directly and indirectly affect their schooling. Their life at home and school is different from that of non-migrant children. Migrants’ children are culturally deprived and they experience various forms of economic, social and educational deprivation and marginalisation. Home challenges feed into school challenges making their life at home and school unbearable. Some of these educational challenges are not unique to migrants’ children in Zimbabwe as the chapter illuminates, but the context of marginalisation of Zimbabweans in Bulilima and Mangwe makes the experiences of migrants’ children complex and problematic. They are culturally disadvantaged and experience all types of deprivation ranging from economic, social, symbolic and institutionalised cultural capital. At home, they lack educational support and at school face ill-treatment by teachers who act favourably towards children of non-migrant parents. Migrants’ children are between a rock and a hard surface though they have developed their funds of knowledge that help them adapt to the challenging situations.